Evaluating the Environmental Footprint of Food Packaging using Lifecycle Assessment (Global Journal of Science Frontier Research, 2019)
Rising consumption of packaged instant foods has escalated environmental problems caused by packaging waste. Using lifecycle assessment (LCA) methodology, this study measures the benefits of applying green packaging technology to ramen noodle packaging in South Korea in 2015. Our LCA method observes the procedures and requirements of the International Organization for Standardization 14044 and the European Community Product Environmental Footprint Guide (ECPEF). Results show that the use of ink and liquefied natural gas used to produce food packaging cause the main environmental impact. Reducing the number of colors on the packaging is the most feasible way to mitigate environmental consequences. Also, up to 16,900 South Koreans could have reduced exposure to human toxicity (non-cancer) if all ramen packaging in South Korea in 2015 had fewer colors.
Keywords: lifecycle assessment; product environmental footprint; food packaging film; gravure printing; potential environmental impact